Optimization of fermentation conditions to increase the production of antifungal metabolites from Streptomyces sp. KN37 - Xiaoyue Yang; Lijing Yuan; Muhammad Zeeshan; Chuntian Yang; Wen Gao; Guoqiang Zhang; Chunjuan Wang (Microbial Cell Factories)
Abstract The bacterium Streptomyces sp. KN37 was isolated from the soil of Kanas, Xinjiang. The broth dilution of strain KN37 has a strong inhibitory effect against a variety of crop pathogenic fungi. However, in practical applications, its effective biological activity is limited by medium formulations and fermentation conditions. In this study, we used the response surface method to optimize the fermentation medium and conditions of the strain KN37, for investigating the reasons for the enhanced biological activity at both the metabolic and transcriptomic levels. The results of the Plackett-Burman design showed that millet, yeast extract, and K2HPO4 were the key factors influencing its antifungal activity. Subsequently, optimization by the response surface methodology yielded the final fermentation conditions as: millet 20 g/L, yeast extract 1 g/L, K2HPO4 0.5 g/L, rotation speed 150 r/min, temperature 25 °C, initial pH 8, fermentation time 9 d, inoculation amount 4%, liquid volume 100 mL. The antifungal effect of the optimized strain fermentation dilution was significantly enhanced, and the antifungal rate of R. solani increased from 27.33 to 59.53%, closely aligning with the predicted value of 53.03%. The results of HPLC-MS/MS and transcriptomic analysis revealed that the content of some secondary metabolic active substances in the fermentation broth of KN37 was significantly different from that of the original fermentation broth. Notably, the content of 4- (diethylamino) salicylaldehyde (DSA) was significantly increased by 16.28-fold while the yield of N- (2,4-dimethylphenyl) formamide (NDMPF) was increased by 6.35 times. Transcriptomic analysis further elucidated molecular mechanisms behind these changes with the expression of salicylic acid dehydrogenase (SALD) was significantly down-regulated, which was only 0.48 times compared to that before optimization. This research successfully optimized the fermentation process of strain KN37 providing a strong foundation for the actual production and application of strain KN37 in agriculture.